Face and Politeness Phenomena in the Changing China - Aziz, E Aminudin (UI Scholars Hub, 2005)
This study aims to investigate the Chinese perceptions about the traditional Confucius concepts mianzi/lian ‘face’ in the context of the world that is changing. In particular, the study focuses on how such perceptions are reflected in their interpersonal communication. Data was collected through direct semi-structured interviews with the respondents, guided by a set of questions regarding the situations they might hypothetically find themselves. Shanghai was chosen as the site for this study because, among other places in China, it has undergone considerable changes. 100 Shanghainese were involved in the study; 50 were city dwellers and 50 villagers, representing their various social backgrounds. The data were analysed by using the Chinese cultural notions underlying the concepts of face: relational, communal, hierarchical, and moral. Analyses show that the respondents often avoid conflicts with their interlocutors, even if they were put in very unfortunate circumstances. These face-favouring acts are indicative of their closed observance of the norms and hence the concepts of face, by which they could gain, maintain, and enhance their own face. In return, they would be regarded as members of the society with polite behaviours and with other good moral characters. The study concludes that although China is changing, the conceptions and practices of the traditional concepts mianzi/lian “face” among Chinese have remained constant. This is because into these concepts are attached the most basic concepts of humanity; the absence of the concepts of face in the mind of human beings can mean the loss of humanity as a whole.